Pharmacogenetics of cardiac inotropy. (November 2014) - Lymperopoulos, Anastasios; Garcia, Dilayda; Walklett, Karlee
The ability to stimulate cardiac contractility is known as positive inotropy. Endogenous hormones, such as adrenaline and several natural or synthetic compounds possess this biological property, which is invaluable in the modern cardiovascular therapy setting, especially in acute heart failure or in cardiogenic shock. A number of proteins inside the cardiac myocyte participate in the molecular pathways that translate the initial stimulus, that is, the hormone or drug, into the effect of increased contractility (positive inotropy). Genetic variations (polymorphisms) in several genes encoding these proteins have been identified and characterized in humans with potentially significant consequences on cardiac inotropic function. The present review discusses these polymorphisms and their effects on cardiac inotropy, along with the individual pharmacogenomics of the most important positive inotropic agents in clinical use today. Important areas for future investigations in the field are also highlighted.